Homoclinic Solutions for a Class of Nonlinear Difference Equations - Ali Mai (Journal of Applied Mathematics, 2014)
We prove the existence of homoclinic solutions of a class of nonlinear difference equations with superlinear nonlinearity by using the generalized Nehari manifold approach. For the case where the nonlinearity is odd, we obtain infinitely many homoclinic solutions of the equations. Recent results in the literature are generalized and improved.